2020
DOI: 10.1186/s43055-020-0135-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance spectroscopy in pediatric brain tumors: how to make a more confident diagnosis

Abstract: Background: Non-invasive diagnosis of pediatric brain tumors can be challenging due to diverse tumor pathologies and similar imaging appearances. Magnetic resonance spectroscopy (MRS), when combined with high spatial resolution anatomic imaging obtained with conventional magnetic resonance imaging (MRI), provides metabolic information within the lesion as well as the surrounding tissue. The differentiation of neoplastic from non-neoplastic lesions and low-grade from high-grade neoplasms is essential for determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…At short TE, mI/Cr ratio of 1.15 was tested as a cut value for diagnosing tumor with sensitivity [100%] and specificity [95%]. Attia et al [3] reported an increase of choline and reduction of NAA at the long TE. This suggested that a larger loss of neuron function and larger membrane turnover characterizes the neoplastic than nonneoplastic processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At short TE, mI/Cr ratio of 1.15 was tested as a cut value for diagnosing tumor with sensitivity [100%] and specificity [95%]. Attia et al [3] reported an increase of choline and reduction of NAA at the long TE. This suggested that a larger loss of neuron function and larger membrane turnover characterizes the neoplastic than nonneoplastic processes.…”
Section: Discussionmentioning
confidence: 99%
“…It was considered the corner-stone for the diagnosis of brain tumors in many cases. However, confident differentiation of neoplastic from non-neoplastic brain lesions or low from high-grade tumors is problematic with conventional MRI [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that MRS provides information necessary for differentiating, tuberculosis, lowgrade and high-grade gliomas, brain abscess and many more. Several previous studies have been carried out to investigate the sensitivities and specificities of various metabolite ratios for diagnosing and differentiating various brain lesions 11,12 . Onyambu et al studied the use of MR spectroscopy and its assistance to the radiologist in diverse clinical presentations 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Pathology is the key to understanding and diagnosing cancer [ 142 , 143 ]. Therefore, it is essential to obtain an accurate diagnosis to determine the best treatment plan [ 144 ]. That is why ultrasounds need image classification and object recognition algorithms that use deep learning to obtain precise results.…”
Section: Ai In Brain Tumor Imagingmentioning
confidence: 99%